Increasing Community Participation in Sustainable Waste Management through Waste Banks - Ivakdalam, Lidya Maria (Agrikan Jurnal Agribisnis Perikanan, 2022)
Waste management through waste banks in an area will have an impact on the community and the environment of the area itself. Waste management can run well if there is participation from various parties, including the community. This paper aims to analyze the concept of waste and waste management and processing methods, analyze the concept of waste bank systems and mechanisms in providing economic and environmental benefits, analyze what factors influence community participation in waste management through waste banks. The results of the study show that waste management consists of reducing waste and handling waste. Waste reduction includes reducing landfill waste, recycling, and re-managing the waste. Communities as waste producers are incorporated in waste banks and carry out activities of collecting, sorting, and saving economic value inorganic waste in waste banks. Then the waste is sold to the waste dealer and the waste bank gets money from the sale which is then deposited into the community's savings according to the purchase price of the waste from the community. Factors that influence community participation in waste management through waste banks are the individual characteristics of the waste bank community, environmental support for waste banks and public perceptions of waste bank governance.